2016
DOI: 10.1186/s40345-016-0050-8
|View full text |Cite
|
Sign up to set email alerts
|

Biological rhythms are independently associated with quality of life in bipolar disorder

Abstract: BackgroundEvidence suggests that patients with bipolar disorder (BD) experience biological rhythm disturbances; however, no studies have examined the impact of this disruption on quality of life (QOL). The aim of this study is to investigate the influence of biological rhythm, depressive symptoms, sleep quality, and sleep medication use on QOL in BD.MethodsEighty BD subjects (44 depressed and 36 euthymic) completed questionnaires assessing QOL (WHOQOL-BREF), biological rhythm disruption (BRIAN), depressive sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 46 publications
1
21
0
2
Order By: Relevance
“…Additionally, previous studies have considered disruptions of biological rhythm as a single symptom, or were conducted only in patients with bipolar disorder. 14,20,21,28,29 Only one recent study evaluated the effect of specific biological rhythm domains on unipolar depression, finding significant disruption in all biological rhythm domains (sleep, activity, social, and eating) and BRIAN-Total score both in patients with MDD and in those with bipolar disorder, compared to healthy controls. 21 However, this study was population-based, only included young adults (age 18-24 years), and did not take into consideration drug use or other confounders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, previous studies have considered disruptions of biological rhythm as a single symptom, or were conducted only in patients with bipolar disorder. 14,20,21,28,29 Only one recent study evaluated the effect of specific biological rhythm domains on unipolar depression, finding significant disruption in all biological rhythm domains (sleep, activity, social, and eating) and BRIAN-Total score both in patients with MDD and in those with bipolar disorder, compared to healthy controls. 21 However, this study was population-based, only included young adults (age 18-24 years), and did not take into consideration drug use or other confounders.…”
Section: Discussionmentioning
confidence: 99%
“…BRIAN was validated in patients with mood disorders and provides comprehensive data. Studies using this instrument found that biological rhythm disturbances influence psychosocial functioning, 18 the severity of depression, 19 and quality of life 20 in patients with mood disorders. A recent study assessed the disruption of biological rhythm in a community sample of young adults with mood disorders (major depression and bipolar disorder), 21 while others were conducted including only patients with bipolar disorder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Furthermore, biological rhythm impairment in adults has been associated with poor functioning and quality of life. 4 Therefore, it is essential to have an assessment instrument for kids, to allow a better understanding of the reactions and the effects that this disturbance may have on our body and mental health in children.…”
Section: Introductionmentioning
confidence: 99%
“…Might they be more effective in patients with a tendency toward staying up late (so‐called evening chronotype – which some , but not all , studies have found more common in patients with bipolar disorder)? Could amber lenses, already demonstrated to be capable of preserving melatonin production , help to stabilize the biological rhythm disturbances recently shown to lower quality of life in bipolar disorder ? Hopefully, the Norwegian study will spur such research.…”
mentioning
confidence: 99%